The Development of Theme Parks for Tourist Destinations : the Case of Escape Cameron Highlands, Malaysia - Rashyida Amyra Razali; Sobirov Bobur Baxtishodovich (International Journal on Economics, Finance and Sustainable Development, 2022)
Theme parks are star actors in the tourist industry and play a unique and crucial role in driving tourism demand. Theme parks are the primary drivers of tourism to several destinations and integral components of the tourism product. In addition to a growing number of parks, competition in the market for theme parks is intensifying compared to other leisure activities. In many regions, however, the need for theme parks appears to be reaching saturation, and parks must accommodate increasingly demanding guests. This case study examines the development of new theme parks in Malaysia concerning the planning and implementation of tourism policies for Malaysia. Given the trends of a growing number of theme parks, environmental limits, and increasingly discerning consumer demand, it can be argued that they must optimize their operations to survive in this competitive market.